Flavonoids Derivatives from Arundina graminifolia and Their Cytotoxicity - Shu, Lidan; Shen, Yanqiong; Yang, Liying; Gao, Xuemei; Hu, Qiu-Fen (Asian Journal of Chemistry, 2013)
A new flavonoid, 3(S),4(S)-3',4'-dihydroxyl-7,8,-methylenedioxylpterocarpan (1), together with ten known flavonoids derivatives (2-11), were isolated from the whole plant of Arundina gramnifolia. The structure of compounds 1-11 were elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. Compound 1 was also evaluated for its cytotoxicity against five human tumor cell lines. The results revealed that compound 1 showed high cytotoxicity against HSY5Y cell with IC50 values of 2.2 μM and moderate cytotoxicities with IC50 valves 5-10 μM for other four tested cell lines.